ECOWAS and AfCFTA: Potential short-run impact of a draft ECOWAS tariff offer - Peter Lunenborg; Thomas Roberts (Journal of African Trade, 2021)
This study provides an ex ante short-run impact analysis of tariff liberalisation in the context of the African Continental Free Trade Area (AfCFTA) on the Economic Community of West African States (ECOWAS) customs union regarding tariff revenue and import values. As with other customs union on the continent, ECOWAS negotiates within the AfCFTA as a bloc (including Mauritania). Tariff revenue losses for a scenario with 97% tariff liberalisation (Categories A and B) amount to around USD 262.7 million at the end of the implementation period, representing 12.5% of total tariff revenue, and USD 201.9 million for a scenario with 90% tariff liberalisation (Category A), representing 9.7% of total tariff revenue. This is more than the USD 54 million inferred from estimates by the World Bank (2020), which assumed 90% tariff liberalisation. Tariff losses for ECOWAS are likely to be larger than previously estimated, mainly because ECOWAS negotiates as a bloc and because its selection of sensitive sectors exempted from liberalisation (Category C) is not optimised at the country level to minimise revenue loss. Import increases on account of ECOWAS tariff concessions under the AfCFTA are estimated to be relatively small (1.3-1.8% total increase). As such, the main worry of ECOWAS policymakers, on aggregate, should not be a deluge of African imports competing with regional or domestic production. Further research is needed to understand the distributional impact among ECOWAS countries and on the benefits of other African countries opening market access to ECOWAS exports.
Keywords: 330; ECOWAS; TRIST; AfCFTA; tariff liberalisation; common external tariff